2014
DOI: 10.1111/hdi.12202
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported cognitive functioning and daily functioning in chronic dialysis patients

Abstract: Background Subjective cognitive impairment negatively affects daily functioning, health-related quality of life, and healthcare consumption and is predictive of future cognitive decline in many patient populations. However, no subjective measures of multidimensional cognitive functioning have been evaluated for dialysis patients. Our purposes were to examine (1) the association between patient-reported (subjective) cognitive functioning and objective cognitive functioning and (2) the relationships between subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…Whereas we used a common cut-off value for poor outcome on the mRS (>2) [ 21 – 23 ], there is no such commonly used cut-off value for the iADL. However, loss of independence on any iADL task is usually regarded as an impaired iADL [ 3 , 24 ]. Therefore we have chosen a cut-off value of <8 to indicate poor functional outcome.…”
Section: Patientsmentioning
confidence: 99%
“…Whereas we used a common cut-off value for poor outcome on the mRS (>2) [ 21 – 23 ], there is no such commonly used cut-off value for the iADL. However, loss of independence on any iADL task is usually regarded as an impaired iADL [ 3 , 24 ]. Therefore we have chosen a cut-off value of <8 to indicate poor functional outcome.…”
Section: Patientsmentioning
confidence: 99%
“…The association between frailty and cognitive impairment has been studied in older populations 11 , 12 and patients on hemodialysis (HD) 13 15 , but has not been clearly established in patients on PD. Both frailty and cognitive impairment are barriers to rehabilitation of patients on PD.…”
Section: Introductionmentioning
confidence: 99%
“…39 Our study does show a statistically significant association of the metaconcentration scores with tests of executive function (TMT B), consistent with another study in the dialysis population. 15 This is not surprising, and it raises the possibility of the metaconcentration measurement as an effective proxy/complement to objective tests of executive brain function. This remains to be validated, and so does the metacognition questionnaire in the population with renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have been published to date, in regard to patients with kidney disease, that specifically seek to examine the association between subjective and objective cognition assessments. 15 , 16 The Kidney Disease Quality of Life (KDQOL)−Cognitive Function subscale with 3 questions was shown to be a limited instrument for accurately assessing subjective cognitive function 16 and bore no relationship to the executive function test, which is commonly abnormal in chronic kidney disease. 17 , 18 , 19 More recently, a study found modest correlation between subjective and objective assessments; however, the former was a predictor of the patient’s self-reported measure of activities of daily living, although both subjective reports may well be influenced by negative affectivity.…”
mentioning
confidence: 99%
See 1 more Smart Citation